2006
DOI: 10.1183/09031936.06.00114405
|View full text |Cite
|
Sign up to set email alerts
|

High sensitivity C-reactive protein in asthma

Abstract: Asthma is characterised by chronic inflammation of the airways, but the relevance of high-sensitivity assays for C-reactive protein (hs-CRP), which are known to be a sensitive marker of low-grade systemic inflammation, has not been fully studied in asthma. The objective was to examine serum hs-CRP levels in patients with asthma and their relationship to clinical characteristics and degree of airway inflammation. Serum hs-CRP levels were cross-sectionally examined in steroid-naive (n = 22) and steroid-inhaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
163
4
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(190 citation statements)
references
References 20 publications
17
163
4
5
Order By: Relevance
“…These factors have not been taken into account in previous studies of systemic inflammation in asthma. [1][2][3] We also correlated the systemic-inflammation markers with various clinical measurements, and found significant negative correlation of the systemic-inflammation markers and FEV 1 , FVC, FEV 1 /FVC, and FEF 25-75 . Takemura et al 3 found similar correlations between C-reactive protein and pulmonary function.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These factors have not been taken into account in previous studies of systemic inflammation in asthma. [1][2][3] We also correlated the systemic-inflammation markers with various clinical measurements, and found significant negative correlation of the systemic-inflammation markers and FEV 1 , FVC, FEV 1 /FVC, and FEF 25-75 . Takemura et al 3 found similar correlations between C-reactive protein and pulmonary function.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] We also correlated the systemic-inflammation markers with various clinical measurements, and found significant negative correlation of the systemic-inflammation markers and FEV 1 , FVC, FEV 1 /FVC, and FEF 25-75 . Takemura et al 3 found similar correlations between C-reactive protein and pulmonary function. This implies that impaired respiratory function is associated with higher background systemic inflammation, but it is not certain whether systemic inflammation does influence pulmonary function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A longitudinal association between asthma and subsequent hospitalization for schizophrenia, and adult diagnoses of depression has been reported (Timonen et al 2003;Pedersen et al 2012;Sanna et al 2014), and three longitudinal studies have reported increased rates of bipolar disorder in individuals with asthma (Liang & Chikritzhs, 2013;Chen et al 2014;Lin et al 2014). IL-6, C-reactive protein (CRP) and other inflammatory markers are associated with asthma and eczema (Takemura et al 2006;Arif et al 2007;Rincon & Irvin, 2012). However, to our knowledge there have been no previous studies showing temporal associations between inflammatory markers, atopic conditions and features of hypomania.…”
Section: Introductionmentioning
confidence: 99%